The effectiveness of the SEPTIA model integrating Taneyan Lanjhang local values on elementary students’ social-cultural literacy - Nanda Septiana; Wahono Widodo; Ganes Gunansyah; Gül Erkol Bayram (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to evaluate the effectiveness of the SEPTIA model (Solving Education through Problem, Tradition, and Indigenous Approach) in enhancing fourth-grade students’ socio-cultural literacy in elementary natural and social science studies (IPAS). The model integrates Problem-Based Learning (PBL) with the local cultural values of Taneyan Lanjhang to develop four dimensions of socio-cultural literacy: intellectual (analysis of social issues), social (empathy and tolerance), cultural (appreciation of local values), and collaborative (cooperative problem-solving skills). A quasi-experimental pretest–posttest control-group design was implemented, involving 50 fourth-grade students from two elementary schools in Pamekasan (25 in the experimental group and 25 in the control group). Data were collected using a validated socio-cultural literacy test and structured observation sheets, and were analyzed through paired-sample t-tests, independent-sample t-tests, and Cohen’s d effect size. The results indicate that the experimental group demonstrated a statistically significant improvement in socio-cultural literacy scores compared to both their pre-test performance and the control group (p < .001). The mean score increased from 59.39 to 77.03 in the experimental group, whereas the control group exhibited a comparatively smaller gain. The effect size was large (d = 1.72), indicating a substantial impact of the SEPTIA model. All four dimensions of socio-cultural literacy improved, with the most pronounced gains observed in the social and cultural dimensions. These findings suggest that integrating local cultural values into a PBL framework is an effective pedagogical strategy for enhancing students’ socio-cultural literacy. This study advances culturally responsive and context-based instructional models in elementary education, particularly by fostering social and cultural competencies alongside cognitive development.